Pendampingan Proses Pengajuan Perizinan Berusaha dan Sertifikasi Halal Bagi Pelaku Usaha UMKM Pengolahan Makanan dan Minuman di Kelurahan Krapyak Semarang Barat - Ranitawati, Endang (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This community service activity aims to assist MSME business entrepreneurs in Krapyak Village, Semarang, in creating a Business Identification Number (NIB) using the online Single Submission (OSS) Application. By having an NIB, business actors can directly apply for their products to have a halal certificate, which can be processed through the online halal application, just like processing the NIB. This program was welcomed with enthusiasm by food and beverage processing MSME business actors. By having an NIB and Halal Certificate, business actors can be safer in developing and marketing their products in order to gain more trust from their buyers. Assistance provided to MSME business actors by submitting a self-declaration without charging any fees at all. This assistance cannot be provided to business actors who have businesses with processed products containing meat, however, halal certificates can be submitted through regular or paid channels.